Kandungan Nitrogen Pada Tanah Dalam Plot Ukur Permanen Di Hutan Pendidikan Wanagama I, Gunungkidul - RIFAI, Achmad ([Yogyakarta] : Universitas Gadjah Mada, 2014)
At first Forest Study of Wanagama I was built for the purpose as a sample of model rehabilitation system for critical area in Gunungkidul regency, Yogyakarta. As it’s development it needs evaluation and monitoring of the land quality in the Forest Study of Wanagama I. one of effort in the evaluation and monitoring is the contruction of Permanent Sample Plot (PSP). The purpose of this research is to measure the contents of soil’s Nitrogen in the Permanent Sample Plot plot of land 5, 6, 7, 16 and 18 in the Forest Study of Wanagama I, Gunungkidul. The researcher took the data through 2 phases, they are take the sample if the soil based on the depth of the land 0-10 cm, 10-20 cm, 20-30 cm, and 30-50 cm. the sampel was analyzed in the laboratory through phases destruction, distillation, titration and continued to make calculation by the formula. The data is describe based on the analyzed of the laboratory. Based on calculation of the contain of the soil’s Nitrogen know that the average in upright clusster of the plot five, horizon 0-10 cm 0,374%, 10-20 cm 0,288%, 20-30 cm 0,228%, 30-50 cm 0,168%. Upright clusster of Teak in plot six, horizon 0-10 cm 0,326%, 10-20 cm 0,287%. Upright clusster of Teak in plot seven, horizon 0-10 cm 0,312%, 10-20 cm 0,328%, 20-30 cm 0,096%, 30-50 cm 0,099%. Upright clusster Mahoni in plot sixteen, horizon 0-10 cm 0,416%, 10-20 cm 0,198%, 20-30 cm 0,144%. Upright clusster Legaran plot eighteen, horizon 0-10 cm 0,304%, 10-20 cm 0,295%, 20-30 cm 0,218%, 30-50 cm 0,356%. Data analisis of Nitrogen dapat digunakan sebagai kegiatan pemeliharaan lanjutan Forest Study of Wanagama I.